P08.02 Harnessing T cells to target brain metastasis. (9th September 2021) - Gregory, S R; Fife, C; Williams, J; Carrasco Hope, H; Andreou, T; James, F; Brownlie, R; Newton-Bishop, J; Salmond, R; Lorger, M
Abstract: BACKGROUND: Up to 60% of melanoma patients develop brain metastases (BrM). These patients have a poor prognosis and limited treatment options. Immune checkpoint inhibitors (ICI) targeting Cytotoxic T-lymphocyte-associated protein-4 (CTLA-4) and Programmed cell death protein-1 (PD-1) have revolutionized the treatment of melanoma and their efficacy has been also demonstrated in melanoma BrM. Our group previously demonstrated that ICI (combined α-PD-1 and α-CTLA-4) enhances chemokine-dependent infiltration of cytotoxic T lymphocytes (CTLs) into melanoma BrMs in preclinical models, accompanied by upregulated expression of T cell attracting chemokines in tumours. Notably, CTLs infiltrating BrM expressed only some of the chemokine receptors (CRs) interacting with ICI-induced chemokines in BrM, providing a rationale to over-express the "missing" CRs in T cells to enhance their homing to tumours in the context of adoptive T cell therapy (ACT). MATERIALS AND METHODS: OT-I cells were isolated from OT-I mice and differentiated ex vivo into effector (TEF ) and memory (TCM ) CD8 + T cells. Tumour infiltrating lymphocytes (TILs) from B16 tumour-bearing mice treated with ICI were isolated using magnetic beads, activated and expanded ex vivo . Expression of CRs and activation markers in ex vivo cultured T cells were quantified by qPCR and/or flow cytometry. The migration of human blood CD8 + T cells towards chemokines of interest were measured in ex vivo migration assays. RESULTS: The same CRs that were missing on BrM-infiltrating CTLs in vivo models were also absent from OT-I TEF (CCR7 low /CD44 high /CD62L low ) and TCM (CCR7 high /CD44 low /CD62L high ) cells, as well as from TILs expanded ex vivo for use in ACT. Furthermore, we observed no increase in migration of human T cells towards chemokines interacting with the "missing" CRs in comparison to the baseline migration, suggesting that these CRs are also absent from human T cells. CONCLUSION: Ex vivo expanded T cells that are used in ACT are missing several CRs that are interacting with chemokines upregulated in BrM. We hypothesise that the use of genetically engineered T cells expressing the "missing" CRs in ACT has the potential to enhance ACT efficacy in combination with ICI.